Uji Antikoagulan Alami Ekstrak Kayu Manis (Cinnamomum Burmanni) Menggunakan Metode Lee-White dan Analisis Apusan Darah - Aldiana Astuti; Theresia Mooy (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Coumarin, a key bioactive compound in cinnamon, is known for its anticoagulant, antibiotic, and anti-carcinogenic properties. This study investigates the potential of cinnamon (Cinnamomum burmanni) extract as a natural anticoagulant using both the Lee-White method, for visual observation of clotting time, and blood smear analysis for microscopic evaluation. The research aims to assess the effectiveness of the extract in preventing blood coagulation compared to untreated blood samples. Results demonstrated that blood without any anticoagulant clotted within an average time of 5 minutes and 33 seconds. In contrast, blood treated with cinnamon extract did not exhibit coagulation, indicating a significant anticoagulant effect. Microscopic examination further supported these findings, as the blood cells in the treated samples appeared separated, with no visible aggregation or linkage between the cells. These findings suggest that cinnamon extract has strong potential as a natural anticoagulant, offering a safer and more accessible alternative to synthetic anticoagulants. Further research could explore its applications in medical treatments, particularly in conditions requiring blood thinning or clot prevention. This study highlights the potential of cinnamon as a valuable bioactive agent in the field of biomedical science, especially for anticoagulation therapies.